Inovasi Pengemasan Produk Souvenir bagi Pedagang di Daerah Wisata Tangkahan, Kabupaten Langkat, Provinsi Sumatera Utara - Nasution, Myrna Pratiwi; Pinem, Laura Juita; Sahnan, Muhammad; Irni, Julaili (Jurnal Pengabdian UNDIKMA, 2023)
This community service program aims to increase traders’ the knowledge and skills in the Tangkahan Tourism Village by innovating souvenir products for tourists. The method of implementing this service consists of Socialization, Training, Mentoring and evaluation. There were 20 participants involved in this activity, and they were souvenir traders in the Tangkahan Tourism Village. The evaluation instrument used in this activity was a questionnaire, and analyzed descriptively. The results of this service show that traders in the Tangkahan Tourism Village have knowledge and skills in packaging souvenir products that can be sold to tourists. Apart from that, traders realize that packaging is one of the attractions in stimulating consumer buying interest, especially in tourist areas.